Immobilization of AgCl/Pd Heterojunctions on Nitrogen‐Doped Carbon Nanotubes: Interfacial Design‐Induced Electronic Regulation Enhances Photocatalytic Activity. Issue 66 (27th September 2022) - Gao, Hao; Chen, Zhiliang; Liu, Huade; Lin, Cunbiao; Sha, Linna; Yang, Yun; Zhuang, Guilin; Wang, Xiaojun; Zhan, Wenwen; Han, Xiguang
Abstract: Rationally designing interface structure to modulate the electronic structure of a photocatalyst is an efficient strategy to facilitate the separation and migration of photogenerated charge carriers and improve photocatalytic activity. In this work, a AgCl/Pd heterostructure encapsulated by N‐doped carbon nanotubes (AgCl/Pd@N−C) with a fan‐like morphology assembled hollow tubes was synthesized by pyrolysis of a AgCl/Pd@Bim precursor. The unique interface structure not only increases the number of photogenerated charge carriers, but also provides an effective channel for the separation of electrons and holes, which have been proved by density functional theory (DFT) calculations. As expected, the obtained AgCl/Pd‐3@N−C exhibited greatly enhanced conversion efficiency and recyclability toward the photocatalytic oxidative coupling of amine under blue‐light irradiation. Abstract : From amine to imine more easily : A fan‐like hollow N‐doped C‐coated AgCl/Pd heterostructure has been synthesized by pyrolysis of a AgCl/Pd@Bim precursor under argon. The interface effect of the AgCl/Pd heterostructure efficiently regulates the electronic structure and accelerates the separation efficiency of photogenerated carriers, leading to excellent photocatalytic activity toward oxidative coupling of amine to imine.